UNDERSTANDING MICROCONTROLLERS AND ROBOTICS THROUGH THE APPLICATION OF INQUIRY METHODS IN BASIC ELECTRONICS COURSES - Cut Susan Octiva; Maryadi, Maryadi; Dikky Suryadi; Nursalim, Nursalim; T. Irfan Fajri (Jurnal Cakrawala Ilmiah, 2024)
This analysis aims to explain the understanding of microcontrollers and robotics through the application of inquiry methods in basic electronics courses. The type of research used is classroom research. The sample of this study was 40 private campus students in Medan City who were taken randomly. This quantitative method uses inquiry methods learning model. The results of the study indicate that the application of the inquiry method can make students understand microcontrollers and robotics in basic electronics courses